PENYULUHAN FISIOTERAPI KOMUNITAS: PENINGKATKAN PENGETAHUAN TENTANG PENCEGAHAN CEDERA PADA PENGGIAT HOBI VOLI DI KELURAHAN TUNJUNGSEKAR - Merianti, Nisfah; Nungki Marlian Yuliadarwati; Eleonora Elsa Sucahyo (Rena Cipta Mandiri, 2025)
Introduction: Volleyball is a sport played by two teams of 6 players each. Volleyball games are played by hitting the ball until it falls into the opponent's area. Volleyball can be played on various forms of courts such as grass, wood, sand or artificial floor surfaces. Objectives: Counseling aims to educate the gymnastic sports community about the description of injuries, causative factors, symptoms, prevention and management of injuries at home. Methods: The method provided is counseling to the community in the form of health promotion about the description of injuries, causal factors, symptoms, prevention and management of injuries at home using leaflet media. conduct pre-post tests to measure the level of community knowledge. Conclusion: From the gymnastic sports community physiotherapy activities carried out on October 19, 2024 at the Multipurpose Field RW 4 Kelurahan Tunjungsekar showed significant results in increasing participant knowledge before and after counseling. This increase shows the effectiveness of counseling in providing a better understanding of injury prevention practices.